(untitled) (Research, Society and Development, 2020)
There is a growing consumer demand for natural foods, and it is of great interest to develop and produce natural and effective substances for food preservation, replacing synthetic preservatives. The growth of bacteria can occur in food due to environmental conditions during handling and storage, even if good manufacturing practices have been observed. This can cause losses for the industry, also becoming a risk of contamination to the consumer, being necessary to develop new techniques for controlling these sources of contamination. Lactic acid bacteria are known for their benefits to the organisms of those who consume them and for the ability to produce, under appropriate conditions, natural antimicrobial compounds, which can be used as biopreservatives in food and contribute to the increase of shelf life. Bacteriocins are proteins or peptides produced in ribosomes that have the capacity to act against certain pathogens, preventing their multiplication in products during the periods of storage and distribution. The aim of this review is to present the main bacteriocin-producing microorganisms, the forms of production, as well as the techniques by which these bioproducts have been applied in the biopreservation of food products and the results obtained. Biopreservation using bacteriocins has been studied and established as a new and important method, however it is necessary to search for production processes of these bacteriocins on a larger scale and with cost reduction, so that their potential can be increasingly explored by science and industry. Studies related to mechanisms of action and applications in food are also necessary in order to support the decisions of regulatory agencies.